The interdisciplinary decision problem: Popperian optimism and Kuhnian pessimism in forestry - Persson, Johannes; Thorén, Henrik; Olsson, Lennart (Ecology and society, 2018)
Interdisciplinary research in the fields of forestry and sustainability studies often encounters seemingly incompatible ontological assumptions deriving from natural and social sciences. The perceived incompatibilities might emerge from the epistemological and ontological claims of the theories or models directly employed in the interdisciplinary collaboration, or they might be created by other epistemological and ontological assumptions that these interdisciplinary researchers find no reason to question. In this paper we discuss the benefits and risks of two possible approaches, Popperian optimism and Kuhnian pessimism, to interdisciplinary knowledge integration where epistemological and ontological differences between the sciences involved can be expected.